Necessary and sufficient conditions for the invertibility of nonlinear differentiable maps - Slyusarchuk, V. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We establish necessary and sufficient conditions for the invertibility of nonlinear differentiable maps in the case of arbitrary Banach spaces. We establish conditions for the existence and uniqueness of bounded and almost periodic solutions of nonlinear differential and difference equations.